Islamic law: an introduction - Laldin, Mohamad Akram (Research Centre, International Islamic University Malaysia, 2006)
This work is an attempt to provide some light into the basic principles of Islamic law in order to understand the purpose of the revelation of rulings in Islam. This understanding is very important to be understood particularly by students and researchers in the field of islamic law. This book also examines five important legal maxims, namely: al-umur bi maqasidiha (matters determined according to intention), al-yaqin la yazulu bi al-shakk (certainty cannot be removed by doubt), al-mashaqqah tajlubu al-taysir (hardship begets facility), la darara wa la dirar (harm shall not be inflicted nor reciprocated) and al-'adah muhakkamah (custom as arbitrary). Theese are considered as supporting sources of Islamic law. In the last part of the work, the development of Islamic from the time of the Prophet (pbuh) till the present is discussed. Finally, the work outlines about the present state of Islamic law and provides some suggestions for the way forward. It is hoped that this work will shed some light for those who are interested in understanding the basics of Islamic law. The author would like to thank the International Islamic University Malaysia for ganting him sabbatical leave and financial assistance for the realisation of this work.